PERBANDINGAN PENGARUH OLAHRAGA ZUMBA DAN CARDIO DANCE TERHADAP FLEKSIBILITAS DAN DAYA TAHAN OTOT - Hanny Hardiyani, - (2019)
The purpose of this study is there are differences in the influence of Zumba and cardio dance on increasing flexibility and muscle endurance. The method used in this study is quasi-experimental with pretest and posttest control group design. The sample used was 30 UPI Nursing students divided into two groups of 15 members, the first group was given the treatment zumba and the second group the treatment cardio dance each with the purposive sampling. The instrument used in this study are flexibility test with sit and reach and muscle endurance with sit up test. Analysis of data used Paired Sample T-Test and Independent Sample T-Test. The results of this study were analized with Paired Sample T-Test that there is effect of zumba and cardio dance influence to increased on flexibility and muscle endurance. Later in Independent Sample T-Test on the research that there is insignificant between is no difference in the influence of Zumba and cardio dance on flexibility and muscle. Recommendations from the study are hoping further research can use samples that have already advanced and begginers in order to compare the physical fitness level. Keywords: Zumba, cardio dance, flexibility, muscle endurance